State Aid and Bank Intervention: The ING Illiquid Assets Back-up Facility (IABF) - Sweder van Wijnbergen; Leontine Treur (Tinbergen Institute, 2011)
The ING Illiquid Assets Back-up Facility announced January 2009 was a SWAP-based insurance to reduce ING's exposure to Alt-A related risk. Did the deal involve state aid? Usingmarketprices to evaluate the SWAP directly is impossible because markets for Alt-A based CDOs had collapsed. We therefore assess the deal's impact on the market's valuation of ING to answer the question. We need to correct for two concurrent events: the announcement of the fourth quarter results and the CEO. We find state aid to be between 1.1 and 2.2 b exteuro. Thus the European Commission's estimate that the IABF entails b exteuro 5 state aid is at variance with the assessment derived from market based valuations. Moreover, the intervention only had asignificant impact on equity values and apparently not on debt values, indicating that ING was sufficiently capitalized.
Keywords: G21; G18; 330; bank intervention; asset swap; guarantees